Comparative Analysis of Tannins in the Rhizomes of Great Burnet (Sanguisorba officinalis L.) - Mukhametgaliev N.R.; Idrisova G.I.; Gilazieva G.Z. (Учёные записки Казанского университета: Серия Естественные науки)
Quantitative analysis of the content of tannins in the rhizomes of great burnet (Sanguisorba officinalis L.) was performed using Leventhal’s permanganometric method, its Kursanov's modification, and spectrophotometry. Advantages and disadvantages of the methods used were discussed to determine the quantitative content of tannins in the active parts of different plants. New locations of S. officinalis populations in various regions of the Republic of Tatarstan were detected. The discovered populations differ in terms of habitat conditions. It was revealed that S. officinalis at the territory of the Republic of Tatarstan can be both light and shade demanding. The quantitative characteristics of tannins in the active parts of S. officinalis from two populations were investigated. The methods used to determine the content of tannins gave different results. It was found that the populations of S. officinalis differ in time when they reach the maximum content of tannins, which depends on the phase of vegetation and the dynamics of accumulation of tannins.